[H.R. 673 FULL SUPPORTED] (Tufts Archival Research Center, 2007)
Copy; Letter from Romeo E. Spaulding, President of the International Association of Black Professional Fire Fighters to Representative Rich Boucher pledging his support for a bill proposed by Boucher regarding fire safe cigarettes. Asserts that fires often severely affect the black community and thus this is a issue he fully endorses.